THE EFFECT OF DIGITAL SKILLS ON E-WORKER PRODUCTIVITY AND THE MEDIATING EFFECT OF WORK EFFORT - Ervina Maulida; Sugeng Ahmad Riyadi; Ditha Riyansa; Adnan Kasofi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study is likely to make a positive contribution, particularly in increasing the productivity of virtual workers and as an evaluation material for companies looking to further optimize their workers' digital skills to produce more productive work results. This study used a purposive non-probability sampling method and a quantitative approach by E-survey to collect a complete dataset of 387. The SPSS 26 was used to inspect all items’ validity and reliability in the research instrument. To assess the overall structural model, confirmatory factor analysis (CFA) was utilized, and to identify the amount to which all variables observed were connected to the underlying latent components, and it used a structural equation model with AMOS. The proposed theoretical model results revealed that the Goodness of Fit Index (GFI) score is 0.961 with 0.070 in RMSEA and 0.039 in RMR. The NFI value is 0.976 with an AGFI score of 0.927 and a CFA score of 0.984, which satisfy all the criterion values. It is found that digital skills do not have a significant and no direct relationship with E-worker productivity. However, digital skills are found to directly and positively impact the direction, persistence, and intensity of work effort.